Waste-to-Energy and recycling: The role of plant ownership and waste mobility. (15th March 2022) - Levaggi, Laura; Levaggi, Rosella; Marchiori, Carmen; Trecroci, Carmine
Highlights: The debate on the compatibility between WtE and recycling was assessed and discussed. The effect of waste mobility and WtE plant's ownership on waste disposal (welfare) are analysed. Under waste mobility, private ownership may lead to excessive aggregate recycling. In waste autarky, plant ownership is neutral, while recycling and incineration are suboptimal. Mobility may not be Pareto improving for both regions. Abstract: This paper proposes a stylized two-region model to study the joint effect of waste mobility and WtE plant's ownership on waste disposal choices, welfare and environmental quality. The aggregate level of recycling emerging from the mobility/private ownership scenario is excessive relative to the first best. By contrast, under waste autarky, the institutional configuration of the WtE plant turns out to be neutral and the resulting level of recycling is generally suboptimal. The analysis further shows that mobility may not be Pareto improving for both regions, and that the engagement of local authorities in the decision of how much waste to incinerate has a sound economic justification, especially in the presence of old-generation WtE plants. Finally, this work provides new insights into the debate about the relationship between WtE incineration and recycling by suggesting that the two opposing views within such debate are not totally incompatible; rather they capture different dimensions of the problem. In particular, the view that WtE combustion represents an obstacle to recycling is consistent with what is found at the local level when burning waste for energy recovery becomes available. while the view that the two activities are positively correlated is more in line with the findings at the aggregate level.